Associations between cardiac troponin, mortality and subsequent use of cardiovascular services: differences in sex and ethnicity. Issue 1 (30th January 2018) - Winchester, David E; Kline, Kristopher; Estel, Christopher; Mahtta, Dhruv; Taasan, Sean; Peacock, Franck W
Abstract : Background: The impact of cardiac troponin (cTn) testing on the downstream use of cardiovascular services is not well understood. We conducted this large-scale single centre cohort study to investigate the patterns of testing that result from the use of cTn. Methods: We conducted this investigation using data collected between 1 January 2013 and 18 December 2015 from an academically affiliated tertiary care centre. Data from all hospitalised patients evaluated with cTn (Roche Elecsys cTn-T) assay were collected from our integrated data repository and divided into two cohorts: all cTn assays negative (<0.03 µg/L) versus at least one elevated (≥0.03 µg/L). The main outcomes were the frequency of use cardiovascular services and mortality. Results: Among 26 663 subjects, 18.6% had at least one elevated cTn assay; acute myocardial infarction was diagnosed in 3.9% overall. More men received cardiac catheterisation and cardiology consultation (OR 1.29, 95% CI 1.20 to 1.39 and OR 1.45, 95% CI 1.31 to 1.61) while African-American patients were less likely to have either catheterisation (OR 0.85, 95% CI 0.77 to 0.93) or consultation (OR 0.72, 95% CI 0.63 to 0.82) performed. Mortality was associated with detectable cTn (HR 2.05, P<0.0001). Conclusions: Among hospitalised patients evaluated with cTn, we observed patterns of underuse and overuse of cardiovascular services. These patterns may have further relevance when high-sensitivity cTn assays are available in the USA. Sex and race-based disparities in cardiovascular services persist.